E-Learning to Improve Higher Order Thinking Skills (HOTS) of Students - R. Poppy Yaniawati (Intelektual Pustaka Media Utama, 2013)
The role of technology integration on modern learning is essential to optimize the acceleration process in Higher Order Thinking Skills (HOTS). This research describes how to implement e-learning to improve HOTS of students and students’ attitude toward e-learning of mathematics, pre- learning students knowledge, duration of login in website, and correlation of variables with HOTS. The subject is 162 students in semester IV, from two different universities and are relatively different in their pre-learning knowledge. The instrument used in this research consisted of pre-learning knowledge HOTS test, students’ attitude scale and technology (computer and internet) skills self test. Based on analysis of the data, it is concluded that students’ HOTS who have studied through blended learning are much better than other learning (full e-learning and conventional approaches). Students’ HOTS with conventional model is better than full e-learning. However, students’ HOTS with full e-learning is worst than other learning (blended learning and conventional). The attitude of students towards e-learning in both learning approaches (blended learning and full e-learning) is positive. There is no significant difference in students’ attitude to these two learning ways. There is a significant correlation between pre-learning knowledge and students’ HOTS, but there is no significant correlation between students’ HOTS and students’ attitude toward e-learning of mathematics. There is a significant correlation between login duration and students attitude toward e-learning of mathematics. No significant correlation is found between login duration and students’ HOTS.